2004
DOI: 10.1242/dev.01454
|View full text |Cite
|
Sign up to set email alerts
|

A conserved metalloprotease mediates ecdysis inCaenorhabditis elegans

Abstract: Molting is required for progression between larval stages in the life cycle of nematodes. We have identified four mutant alleles of a Caenorhabditis elegans metalloprotease gene, nas-37, that cause incomplete ecdysis. At each molt the cuticle fails to open sufficiently at the anterior end and the partially shed cuticle is dragged behind the animal. The gene is expressed in hypodermal cells 4 hours before ecdysis during all larval stages. The NAS-37 protein accumulates in the anterior cuticle and is shed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 19 publications
(29 reference statements)
1
84
0
1
Order By: Relevance
“…In addition, some of these enzymes are found to be secreted from the glandular system that surrounds the oesophagus and may be particularly important in the latter stages of cuticle removal or ecdysis, with many representing important components of the moulting exsheathment fluid (Albertson and Thomson, 1976;Nelson et al 1983;Bird, 1987). Many of the subgroup V nematode astacin metalloproteases share these cuticle-related expression patterns, i.e., they are found in the excretory duct, pharynx and hypodermal cells (Davis et al 2004;Novelli et al 2004;Suzuki et al 2004;Stepek et al 2010b). C. elegans DPY-31 was found to be expressed throughout the life-cycle in the hypodermal cells (Novelli et al 2004) and in the oesophageal glands (Stepek et al 2010b), whereas the heterologous expression of the B. malayi promoter/ reporter gene revealed predominant expression in the oesophageal gland cells and gut of C. elegans, leading to the suggestion that DPY-31 plays a role in the construction of the nematode cuticle (Stepek et al 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some of these enzymes are found to be secreted from the glandular system that surrounds the oesophagus and may be particularly important in the latter stages of cuticle removal or ecdysis, with many representing important components of the moulting exsheathment fluid (Albertson and Thomson, 1976;Nelson et al 1983;Bird, 1987). Many of the subgroup V nematode astacin metalloproteases share these cuticle-related expression patterns, i.e., they are found in the excretory duct, pharynx and hypodermal cells (Davis et al 2004;Novelli et al 2004;Suzuki et al 2004;Stepek et al 2010b). C. elegans DPY-31 was found to be expressed throughout the life-cycle in the hypodermal cells (Novelli et al 2004) and in the oesophageal glands (Stepek et al 2010b), whereas the heterologous expression of the B. malayi promoter/ reporter gene revealed predominant expression in the oesophageal gland cells and gut of C. elegans, leading to the suggestion that DPY-31 plays a role in the construction of the nematode cuticle (Stepek et al 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…This unidentified enzyme was found in the L3 exsheathing fluid and formed a distinctive refractile ring *20 μm from the anterior tip, a prerequisite to cap removal and exsheathment. Davis et al (2004) demonstrated that recombinant NAS-37 from C. elegans was effective in inducing refractile ring formation on isolated L3 cuticles of H. contortus. This information suggests that the protease in H. contortus exsheathing fluid and its substrate are functionally conserved to NAS-37 from C. elegans.…”
mentioning
confidence: 99%
“…6A). The accumulation of QUA::GFP in the head region is reminiscent of that of the metalloprotease NAS-37 (Davis et al, 2004). QUA::GFP (pLH069) is located in four quadrants along the body, reminiscent of the muscle quadrants.…”
Section: Both Qua Domain and Hog Domain Of Qua-1 Are Secreted And Assmentioning
confidence: 99%
“…Several genes involved in molting have been shown to cycle expression levels through the larval molting cycles during larval development (Davis et al, 2004;Hashmi et al, 2004;Frand et al, 2005). To test whether the transcript levels of qua-1 are also subject to cyclical changes, we conducted a time-course recording of the fluorescent signal in live transgenic worms carrying the transcriptional GFP fusion construct qua-1pro::GFP.…”
Section: Cycles Of Qua-1 Transcription Levelsmentioning
confidence: 99%
See 1 more Smart Citation